Energy Access Inequality in Indonesia: Socio-Economic Impact Analysis of the 2025 Pertamina Case on Fulfilling Citizens' Rights to Fair and Affordable Energy - Syakira, Firda; Fajri, Inayah; Artika, Revalina; Khairunnisa, Selvi Salsabillah (Media Hukum Indonesia (MHI), 2026)
Energy inequality in Indonesia is exacerbated by corrupt practices, as in the "2025 Pertamina Corruption Case". This research analyzes the socio-economic impact of this case as a violation of citizens' rights to fair energy. Using a qualitative-juridical method, the findings show that corruption (e.g., mark-ups subsidy embezzlement) directly impacts poor households, MSMEs, and hinders development in 3T regions. This corruption is proven to violate constitutional rights. The proposed solutions are the reconstruction of energy regulations and fundamental reforms of BUMN governance (GCG).